Simultaneous Effect of Initial Moisture Content and Airflow Rate on Biodrying of Sewage Sludge - Huilinir-Curio, C (Elsevier Ltd, 2015)
The simultaneous effect of initial moisture content (initial Mc) and air-flow rate (AFR) on biodrying performance was evaluated. For the study, a 32 factorial design, whose factors were AFR (1, 2 and 3 L/min kgTS) and initial Mc (59, 68 and 78% w.b.), was used. Using energy and water mass balance the main routes of water removal, energy use and efficiencies were determined. The results show that initial Mc has a stronger effect on the biodrying than the AFR, affecting the air outlet temperature and improving the water removal, with higher maximum temperatures obtained around 68% and the lowest maximum matrix temperature obtained at initial Mc = 78%.Through the water mass balance it was found that the main mechanism for water removal was the aeration, with higher water removal at intermediate initial Mc (68%) and high AFR (3 L/min kgTS). The energy balance indicated that bioreaction is the main energy source for water evaporation, with higher energy produced at intermediate initial Mc (68%). Finally, it was found that low values of initial Mc (59%) improve biodrying efficiency. © 2015 Elsevier Ltd